Response to the article “Bickerstaff brainstem encephalitis, acute transverse myelitis, and acute motor axonal neuropathy: diagnostic and treatment challenges in patients with concomitant syndromes. Clinical observation” - N. A. Suponeva; I. S. Bakulin; A. S. Rizvanova; R. N. Konovalov; Yu. E. Konovalov (Нервно-мышечные болезни, 2018)
.